Seasonal Variation in Microbial Contamination of Various Food Items in Karachi: Microbial Contamination of Various Food (Biological Sciences - PJSIR, 2021)
The present study was carried out to investigate the effects of seasonal variation on the microbiological quality of various food items collected from Karachi, Pakistan. A total of two thousand food samples were collected during summer, winter, spring, and autumn season and analyzed for total bacterial count (TBC), total Califarm count (TCC), Fecal califarm count (FCC), mould and yeast count (MYC) and Salmanella spp. The highest percentage of unfit samples was recorded during summer i.e. 25.95%, while the lowest value 11.24% and samples were found unfit in terms of total bacterial count during winter. Furthermore, 24.25% of samples were unsatisfactory during the autumn season followed by spring i.e. 14.54%. Moreover, findings further demonstrated that MYC was observed higher in all seasons as compared to TBC. None of the samples was found positive for Salmanella spp.